Teachers Working in Special Schools in Scotland Acting with Practical Wisdom: Supporting Children with Additional Needs in COVID-19 Lockdown - Daniela Mercieca; Duncan P. Mercieca; Kumara Ward (MDPI AG, 2021)
The COVID-19 lockdown has substantially disrupted the established facets of teacher engagement with their students, and, given the significance of this multidimensional interaction, it brings into question what we know as teachers' identity. The lockdown has offered a dilemmatic context where the processes of teaching and learning and being(s) a teacher are being re-visited and re-negotiated. This paper looks specifically at the perceptions of two teachers of their lockdown experience working within a special education context in Scotland, supporting children with disabilities and/or learning difficulties while at home. The question that this paper addresses is: what is the understanding of these two teachers of their role in a specialised educational context while in COVID-19 lockdown? This paper uses 'practical wisdom' (also known as phronêsis) as its theoretical basis, where the focus is on teachers' judgements at precisely those moments where guidelines and procedures are unclear, and the criteria open to multiple interpretations. The COVID-19 pandemic certainly provided this context. Richard Smith's interpretation of phronêsis as 'attentiveness' are central to this paper. In-depth interviews carried out with teachers are analysed through this theoretical framework and two themes are discussed.